A Convenient Catalytic Method for the Synthesis of Pyridines with Henna and Pyrazole Moieties using Cooperative Vinylogous Anomeric‐Based Oxidation. Issue 23 (17th June 2022) - Dashteh, Mohammad; Afsar, Javad; Baghery, Saeed; Zolfigol, Mohammad Ali; Khazaei, Ardeshir; Moosavi‐Zare, Ahmad Reza; Alonso, Diego A.; Khoshnood, Abbas
Abstract: In this work, [Fe3 O4 @SiO2 (CH2 )3 ][DABCO‐H][C(CN)3 ]2 was prepared, identified by various analyses such as FT‐IR, EDX, SEM coupled EDX (SEM mapping), XRD, FE‐SEM, TEM, TGA, DTG, ICP and VSM and used as a nanomagnetic catalyst for the synthesis of henna‐based benzopyrazolo[3, 4‐b]quinolindiones via cooperative vinylogous anomeric based oxidation under solvent‐free condition. Some of these products are new and reported for the first time. Abstract : In this work, [Fe3 O4 @SiO2 (CH2 )3 ][DABCO‐H][C(CN)3 ]2 was prepared, identified and used as a nanomagnetic catalyst for the synthesis of henna‐based benzopyrazolo[3, 4‐b]quinolindiones via cooperative vinylogous anomeric based oxidation under solvent‐free condition.